Evaluation of Corn Response to In-Season Potassium Fertilization Using Dry Fertilizer - D. A. Charbonnier; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2021)
In-season application of potassium (K) fertilizer may offer an alternative to remediate deficiencies developed during the growing season. The objective of this study was to determine corn response to topdress K application under deficient K soil conditions. Treatments included a control and 50 lb K2O/a in-season broadcasted at the V8 growth stage. The fertilizer source was potassium chloride (KCl). Measurements collected were plant biomass and tissue nutrient concentration at reproductive stage (R6), and grain yield. Potassium fertilization increased yield at the location evaluated in this study. The in-season fertilized treatment produced higher yield compared to the control (P<0.09). The late K fertilization had higher K concentration and uptake in the plant at R6 (P<0.06) with the same plant biomass as the control treatment. Also, broadcasting KCl at V8 resulted in a higher K/Mg ratio late in the season (R6). Preliminary results of this study suggest that in-season applications using dry K fertilizers could be used when pre-plant fertilization was not done. Nevertheless, for a dry growing season, corn response might be limited.
Keywords: potassium; in-season; corn